An analytical Study of Accomplishing Educational Duties Reality of the Physical Education Lesson from Baghdad / Al Kurk School Teachers’ Point of View - Zidan, Muhammed; Naji, Diaa (Journal of Physical Education, 2019)
The aim of the research is to build a measure of educational duties’ achievement of physical education lesson from the point of view of Baghdad / Karkh school teachers. The researchers used the descriptive method in the survey method. The sample included (700) primary school physical educators from general directorate of education/ Baghdad; 1st Karkh, 2nd Karkh and 3rd Karkh the subjects were (205). The researchers proposed (21) items that was presented to (20) experts, thus (8) items were deleted (8) leaving only (13) items. The researchers applied the final scale on the subjects to come up with the results of the research.